Pengaruh Tingkat Pendidikan, Jumlah Penduduk dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi Di Kabupaten Batang Hari - Sri Rosmawati; Andi Arisman (Universitas Batanghari Jambi, 2020)
The purpose of this study was to determine the effect of Education Level, Population and Government Expenditure on Economic Growth in Batang Hari Regency. The analytical method used is quantitative using multiple linear regression analysis tools. Testing the significance of the influence of the variable Education Level (X1), Total Population (X2) and Government Expenditure (X3) as independent variables, and Economic Growth (Y) as the dependent variable was carried out by the t test and F test. The results showed that the t test can be seen from the coefficients table that the independent variable does not have a significant effect on the dependent variable. The results of hypothesis testing on the variable Level of Education, Total Population and Government Expenditure on Economic Growth show that the value of Fcount> Ftabe ((7,395> 4.76) is obtained. Economic Growth in Batang Hari Regency The resulting Adjusted R Square is 0.681. It can be concluded that the percentage of the Effect of Education Level, Population and Government Expenditures on Economic Growth in Batang Hari Regency is 68.1% and 31.9% is influenced by other variables not examined in this study.